Eat-clean-repeat: reef manta rays (Mobula alfredi) undertake repetitive feeding-cleaning cycles at an aggregation site in Seychelles - Newsome, Rachel J.; Grimmel, Henriette M. V.; Pouponeau, Dillys K.; Moulinie, Ellie E.; Andre, Amy A.; Bullock, Robert W. (Frontiers in Marine Science, 2024)
To maximise energy efficiency, manta ray (Mobula alfredi, M. birostris) foraging and cleaning behaviours are thought to often be mutually exclusive, whereby individuals will only forage when prey density thresholds are met and will only clean when foraging is too energetically costly (i.e., thresholds are not met). Here, snorkel surveys and remote camera cleaning station footage show reef manta rays (M. alfredi) undertaking repetitive and short-term movements between surface-feeding and cleaning station visits around D’Arros Island, Seychelles. These observations demonstrate that foraging and cleaning behaviours are not mutually exclusive even when prey densities are high. At D’Arros Island, the proximity of cleaning stations to highly productive foraging areas may afford individuals the opportunity to undertake non-foraging activity without incurring significant energy loss from the shifts in behaviour. These data inform a more nuanced understanding of this species’ use of key habitats.